(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to find out the influence of service quality and image owned by PT. Glow Pro Indonesia City of Bandung in determining the interest of consumers to use car care services of PT. Glow Pro Indonesia City of Bandung. The research method used is descriptive and verification method, with an unknown research population and sampling techniques using the iteration method. Respondents in this study were consumers who had used the services of PT. Glow Pro Indonesia City of Bandung. The benefits of this study are used with managerial implications as the next stage for corporate use and subsequent research. The results of this study indicate that Fcount> Ftable, which is 7.51> 3.08 which concludes service quality and brand image can significantly influence consumer interest in using the services of PT. Glow Pro Indonesia City of Bandung. Furthermore, the significance of service quality in influencing consumer interest with tcount> ttable, which is 6.97> 1.65, and can draw the conclusion that service quality can significantly influence consumer buying interest. Brand image in influencing consumer interest with tcount> ttable, which is 5.69> 1.65, and can draw conclusions that brand image can significantly influence consumer buying interest. The influence of the two variables in influencing consumer interest was 76.9 percent with a residual factor of 23.1 percent which was not examined in this study.